Chemical weed control in dry beans (Phaseolus vulgaris L.) in the state of Veracruz México. - Esqueda, Valentín A. (2016)
Two experiments wiht herbicides were carried out during the Fall-Winter seasons of 1990-91 and 1991-92. The objective was to determine the best preemergence and/or postemergence herbicide treatments for controlling the dominant weed species in the residual moisture growing sistem of beans. The experiments were established in the central area of the state of Veracruz, Mexico.In both experiments, treatments were distributed in a CRBD with 12 treatments and four replications. Melampodium divaricatum and Cyperus rotundus were the dominant weed species in both experimental sites. Euphorbia heterophylla and Sorghum halepense were dominant in one location each. In preemergence, the maximum control of M. divaricatum was obtained with alachlor (2 kg a.i./ha) and linuron (2 kg/ha), the last herbicide was also efficient to control E. heterophylla. In postemergence, fomesafen (0.25 kg/ha) showed an efficient control of the two dominant weed species. No treatment controlled C. rotundus, and S. halepense was only controlled with a treatment included fluazifop-butyl. Linuron and alachlor caused toxicity to the bean plants when the residual moisture of the soil was high. However, and contrary to the response observed with these two herbicides, fomesafen caused a higher toxicity when the residual moisture in the soil was low.